Skill analysis training in physical education: A multimedia approach - Williams, E. (1997)
The ability to observe and to accurately analyze movement skills is fundamental to effective teaching in Physical Education (Barrett, 1979; Kelly, Walkley, & Tarrant, 1988; O'Sullivan, Stroot, Tannehill, & Chou, 1989). Unlike coaches who specialize in sport specific movement forms, physical educators are typically confronted with a large variety of movement forms to analyze and diagnose. Although sport-specific training programs have been successful in developing analytic abilities of preservice physical education teachers (Kniffen, 1985; Halverson, 1987; Rush, 1990; Wilkinson, 1986), the variety of movement forms encountered by physical education teachers, as well as the time available to teach qualitative assessment, precludes a sport-specific approach. Recent skill analysis dissertations completed at The Ohio State University (Johnson, 1990; Matanin, 1993) suggest the potential for a mechanical approach to the analysis of skill (Kreighbaum & Barthels, 1990), otherwise referred to as a performance principle approach. Theoretically, developing analytic and diagnostic competencies through a performance principle (mechanical analysis) approach would decrease the time required for students to become competent observers. A multimedia approach as opposed to a lecture approach to instruction offers another means by which the time required to acquire mastery of instructional content may be more efficiently (Falk & Carlson, 1991) and flexibly used. Combining the attributes of multimedia instruction, namely the efficient and flexible use of time, along with a performance principle approach to instruction, offers the potential for a time-efficient means of developing analytic and diagnostic competencies. The purpose of this study therefore was to investigate the effectiveness of a multimedia (laserdisc) performance principle (mechanical analysis) training protocol on subjects' ability to analyze and diagnose throwlike skills. This study also examined the extent to which subjects' analytic and diagnostic skills generalized to untrained throwlike movements.